Comparison of the Effect of Alemtuzumab versus Standard Immune Induction on Early Kidney Allograft Function in Shiraz Transplant Center - A Khalafi-Nezhad; MM Sagheb; F Amirmoezi; Z Jowkar; AR Dehghanian (International Journal of Organ Transplantation Medicine, 2015)
Background: Induction therapy regimens classified as conventional immunosuppressive agents and lower doses of conventional agents combined with antibodies against T-cell antigens have been purposed to prevent acute rejection after renal transplantation. Various induction agents with different doses and durations have been suggested based on the risk profile of patients.